Bijbelgetrouw in leer & leven - Nullens, Patrick (Tijdschrift voor theologie, 2010)
Evangelicalism is a highly diverse Christian movement, yet all parts agree on Scripture's absolute authority in teaching and life. The Bible's own perception of itself is the starting point for this view of Scripture. Furthermore, the evangelical view of the Bible is consistent with the sixteenth-century Reformation. Striking here is the combination between the doctrines on the perspicuity of Scripture and on the priesthood of all believers. It results in a view in which each individual Christian takes on the role of interpreter. The evangelical view draws from two historical sources. First is the pietist and Wesleyan line (seventeenth and eighteenth centuries) that stresses the Bible as book of spiritual renewal and container of the gospel proclaimed to the world. The second is the more dogmatic/cognitive line of the Old Princeton School (eighteenth and nineteenth centuries). For it, the Bible is a reliable written record of divine revelation. Post World War ii neo-evangelicalism adopted this second cognitive approach, especially as answer to the growing impact of liberal Protestant biblical criticism. Yet modernism also permeated the thinking methods of this apologetic zeal. We note significant shifts in evangelical bibliology in the post-modern period. Many evangelical theologians are leaving the path of the Old Princeton School in favour of the pietistic line where they once again stress the transformative power of Scripture. They are strikingly critical of modernity's individualism and stress the hermeneutical import of the community of believers. At the same time they show a growing interest in early church tradition and the old creeds as rules of faith. This gives evangelical theology a Catholic character and a growing interest in ecumenical dialogue that is based on the authority of Scripture and on christocentrism. Yet the question of the consequences of these recent developments still remains. What is tradition's exact place and what are its consequences for ecclesiology?